A flame retardant super hydrophobic coating and use method thereof

By combining the modified polyurethane prepolymer Si-PUA with phosphoric acid modified epoxy acrylic resin and IEM modified nano-silicon dioxide, the problem of insufficient precipitation and hydrophobic properties of the flame retardant in the prior art is solved, and high efficiency is achieved The flame retardant and superhydrophobic coating is suitable for automotive, electronics and other industries.

CN116716034BActive Publication Date: 2024-12-20HUACHANG POLYMER EAST CHINA UNIV OFSCI & TECH

Patent Information

Application Number
CN202310594859.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2024-12-20
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

In actual applications, existing flame retardant water-based coatings may precipitate, resulting in poor flame retardant effect and insufficient hydrophobic performance, making it difficult to meet the high requirements of industries such as automobiles and electronics.

Method used

Using modified polyurethane prepolymer Si-PUA, phosphoric acid modified epoxy acrylic resin and IEM modified nanosilicon dioxide, a low-surface energy coating is formed by spraying, and cross-linking is combined with a photoinitiator to prevent flame retardant from precipitating out. And improve hydrophobic properties.

Benefits of technology

It effectively prevents the precipitation of flame retardant, improves the hydrophobic and flame retardant properties of the coating, and forms a coating with excellent flame retardant and superhydrophobic properties, suitable for high-demand automotive and electronic industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004246835400000021
    Figure BDA0004246835400000021
  • Figure BDA0004246835400000031
    Figure BDA0004246835400000031
  • Figure BDA0004246835400000041
    Figure BDA0004246835400000041
Patent Text Reader

Abstract

The present invention relates to the field of fine chemical technology, and more particularly to IPC C09D163, and more specifically to a flame retardant super hydrophobic coating and its use method. In the present invention, firstly, a low surface energy organosilicon-modified polyurethane prepolymer Si-PUA is synthesized by reacting organosilicon with diisocyanate, and then Si-PUA and P-N halogen-free flame retardant modified epoxy acrylic resin mixed solution are sprayed on the surface of the base to form a low surface energy coating; Then, the nano-silicon dioxide modified by IEM is sprayed on the Si-PUA coating to form a double-layer structure, and cross-linked by a photoinitiator, so as to improve the super hydrophobicity and flame retardant properties of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fine chemicals, in particular to IPC C09D163, and more specifically to a flame retardant super hydrophobic coating and a use method thereof. Background Art

[0002] Coatings are solid materials that form thin films on the surface of objects under certain conditions to protect, decorate or other purposes. With the development of technology and economy, my country has become the world's second largest coatings country. Epoxy resins have excellent effects and have good application prospects on plastics, wood products and metals. They are used in the automotive, electronics, electrical appliances, power and other industries and need to have good flame retardant and hydrophobic properties.

[0003] The existing patent CN201911280242.X discloses a flame-retardant water-based coating and a preparation method thereof. The preparation raw materials include water-based epoxy resin, sodium methylene bisnaphthalene sulfonate, hydroxypropyl methylcellulose, flame retardant, graphene oxide, triethanolamine, and deionized water. Flame retardant and graphene oxide are added to the formula to improve the flame retardant effect. However, in actual application, the flame retardant may precipitate, resulting in a deterioration in the flame retardant effect, and the hydrophobic effect of the coating needs to be improved. Summary of the invention

[0004] In order to solve the problems in the prior art, the first aspect of the present invention provides a flame retardant super hydrophobic coating, whose components include component A and component B; the component A includes modified polyurethane prepolymer Si-PUA, modified epoxy acrylic resin, a photoinitiator and an organic solvent; the component B includes modified nano-silica, a photoinitiator and an organic solvent.

[0005] Preferably, the components of component A, by weight, include 70 to 80 parts of modified polyurethane prepolymer Si-PUA, 15 to 25 parts of modified epoxy acrylic resin, 3 to 8 parts of photoinitiator and 450 to 550 parts of organic solvent; further preferably, it is 75 parts of modified polyurethane prepolymer Si-PUA, 20 parts of modified epoxy acrylic resin, 5 parts of photoinitiator and 400 parts of organic solvent.

[0006] Preferably, the mass ratio of the modified nano-silica to the photoinitiator to the organic solvent in the B component is 95-100: 1-5: 350-450; further preferably, it is 97: 3: 400. Preferably, the modified nano-silica accounts for 0.01-4wt% of the flame retardant super hydrophobic coating.

[0007] Preferably, the modified polyurethane prepolymer Si-PUA is a silicone-modified polyurethane prepolymer Si-PUA.

[0008] Preferably, the preparation method of the silicone-modified polyurethane prepolymer Si-PUA comprises the following steps:

[0009] S1: In a N2 atmosphere at 40-50°C, dibutyltin dilaurate is used to initiate the reaction of polydimethylsiloxane-hydroxyl and isophorone diisocyanate for 2-4 hours to obtain terminal isocyanate polyurethane PDMS-NCO;

[0010] S2: After reacting for 2 to 4 hours, the temperature is raised to 60 to 70° C., pentaerythritol triacrylate is added dropwise to the isocyanate-terminated polyurethane PDMS-NCO, and the reaction is carried out for 2 to 4 hours to obtain a silicone-modified polyurethane prepolymer Si-PUA.

[0011] Preferably, the molar ratio of the polydimethylsiloxane-hydroxyl group to isophorone diisocyanate is (2-3):1; more preferably, it is 2.1:1.

[0012] Preferably, the molar ratio of the pentaerythritol triacrylate to the isocyanate-terminated polyurethane PDMS-NCO is (0.9-1.1):1; more preferably, it is 1:1.

[0013] Preferably, the synthesis route of the organosilicon-modified polyurethane prepolymer Si-PUA is as follows:

[0014]

[0015] Preferably, the modified epoxy acrylic resin is PN halogen-free flame retardant modified epoxy acrylic resin.

[0016] Preferably, the preparation process of the PN halogen-free flame retardant modified epoxy acrylic resin is as follows: dissolving epoxidized m-phenylenediamine AG-601 in 50-200 mL of acetone, then adding phosphoric acid, stirring with an inhibitor, reflux heating to 50-70° C., maintaining for 2-4 hours to obtain a reactant, then rotary evaporating to remove acetone in the reactant, freeze drying to remove moisture in the reactant, and obtaining a light yellow transparent solid; grinding with agate mortar, washing with ethyl acetate to remove unreacted reagents, and rotary evaporating and drying to obtain a light yellow powder, which is named PN halogen-free flame retardant modified epoxy acrylic resin.

[0017] Preferably, the synthesis route of the PN halogen-free flame retardant modified epoxy acrylic resin is as follows:

[0018]

[0019] Preferably, the molar ratio of the epoxidized meta-xylylenediamine to phosphoric acid is (1.8-2.2):1; more preferably, it is 2:1.

[0020] Preferably, the model of the epoxidized meta-xylylenediamine is AG-601.

[0021] Preferably, the phosphoric acid is an 85 wt % phosphoric acid aqueous solution.

[0022] Preferably, the polymerization inhibitor accounts for 0.1% of the sum of the mass of epoxidized meta-xylylenediamine and phosphoric acid.

[0023] Preferably, the polymerization inhibitor includes one or more of hydroquinone, o-methyl hydroquinone, p-hydroxyanisole, p-benzoquinone and 2,6-di-tert-butyl-4-methylphenol.

[0024] In the present invention, phosphoric acid-modified epoxy acrylic resin is used to epoxidize m-xylenediamine, thereby preventing the precipitation of small molecule flame retardants and having good water solubility. The present invention finds that phosphoric acid-modified epoxy acrylic resin epoxidized m-xylenediamine can graft the flame retardant onto the main chain of the epoxy resin, thereby solving the problem of precipitation of phosphoric acid flame retardants due to incompatibility with some coating systems. At the same time, the molecular structure after grafting not only contains PN flame retardant elements, but also contains a large amount of hydroxyl groups, so that the resin has good water solubility and becomes a flame retardant resin matrix for water-based coatings.

[0025] In the present invention, a low surface energy coating is formed by spraying a polyurethane prepolymer Si-PUA modified by silicone, and then a mixed liquid of Si-PUA and PN halogen-free flame retardant modified epoxy acrylic resin is sprayed on the surface of the base layer, thereby improving the hydrophobicity of the coating. The inventors speculate that the polyurethane prepolymer Si-PUA modified by silicone is a low surface energy prepolymer, and the spray liquid mixed with PN halogen-free flame retardant modified epoxy acrylic resin is also a low surface energy spray liquid, which has a large water surface tension and has good hydrophobicity.

[0026] Preferably, the modified nano-silica is nano-silica modified with isocyanoethyl methacrylate (IEM).

[0027] Preferably, the preparation method of the isocyanoethyl methacrylate (IEM)-modified nano-silica comprises: drying the nano-silica in a vacuum oven at 180-220° C. for 1.5-3 h, and then cooling it to 25° C.; dispersing it in ethyl acetate to obtain a nano-silica suspension; then adding IEM and dibutyltin dilaurate to the nano-silica suspension respectively, stirring at 60-80° C. for 3-5 h, and washing and drying to obtain isocyanoethyl methacrylate (IEM-SiO2)-modified nano-silica.

[0028] Preferably, the synthesis route of the nano-silica modified with isocyanoethyl methacrylate (IEM) is as follows:

[0029]

[0030] Preferably, the ratio of the nano-silicon dioxide to ethyl acetate is (0.9-1.1) g:50 mL.

[0031] Preferably, the mass ratio of the IEM, dibutyltin dilaurate and nano-silicon dioxide is 3: (0.01-0.03): (0.9-1.1).

[0032] In the present invention, by spraying IEM-modified nano-SiO2, the hydrophobic property of the coating is further improved to form a super-hydrophobic structure. The inventors creatively discovered that the IEM-modified nano-SiO2 suspension changes the three-dimensional porous structure of the solid surface, forms a micro-nano-scale concave-convex rough structure on the coating surface, and can produce the so-called "lotus effect", making the coating surface super-hydrophobic.

[0033] Preferably, the photoinitiator includes one or more of photoinitiator 1173 , photoinitiator TPO, and photoinitiator 184 .

[0034] Preferably, the organic solvent comprises ethyl acetate.

[0035] In the present invention, the flame retardant properties of the coating are improved by adding silicone-modified polyurethane prepolymer Si-PUA, PN halogen-free flame retardant modified epoxy acrylic resin, and IEM-modified nano-SiO2. The present invention unexpectedly found that in addition to the certain flame retardant effect of the PN halogen-free flame retardant modified epoxy acrylic resin itself, the silicon particles in Si-PUA and IEM-modified nano-SiO2 have a greater influence on the formation of a stable carbon layer, improving the stability of the carbon layer, thereby effectively preventing the release of combustible gas, and can also block the downward propagation of oxygen and heat, achieving the purpose of flame retardancy.

[0036] A second aspect of the present invention provides a method for using a flame retardant super hydrophobic coating, comprising the following steps:

[0037] M1: Dissolve the Si-PUA prepolymer, PN halogen-free flame-retardant modified epoxy acrylic resin and photoinitiator in component A in an organic solvent to prepare a resin dispersion; then spray the resin dispersion onto the substrate using a paint sprayer, wait for 5 to 8 minutes, and obtain a modified polyurethane layer of 5 to 10 μm;

[0038] M2: After 5 to 8 minutes, the nano-silica modified with isocyanoethyl methacrylate (IEM), photoinitiator and ethyl acetate in component B are prepared into solution B using the same paint sprayer, sprayed evenly onto the modified polyurethane layer, and cured under ultraviolet light for 3 to 5 minutes to prepare a flame-retardant super-hydrophobic coating.

[0039] Preferably, the substrate includes one or more of aluminum and fiberglass.

[0040] Beneficial Effects

[0041] 1. In the present invention, a low surface energy coating is formed by spraying a silicone-modified polyurethane prepolymer Si-PUA, and then spraying a mixed solution of Si-PUA and PN halogen-free flame-retardant modified epoxy acrylic resin on the surface of the base layer, thereby improving the hydrophobic performance of the coating.

[0042] 2. In the present invention, by spraying IEM-modified nano-SiO2, the hydrophobic property of the coating is further improved to form a super-hydrophobic structure.

[0043] 3. In the present invention, phosphoric acid-modified epoxy acrylic resin is used to epoxidize m-xylylenediamine, thereby preventing the precipitation of small molecule flame retardants and having good water solubility.

[0044] 4. In the present invention, the flame retardant properties of the coating are improved by adding silicone-modified polyurethane prepolymer Si-PUA, PN halogen-free flame retardant modified epoxy acrylic resin, and IEM-modified nano-SiO2.

[0045] 5. In the present invention, firstly, a low surface energy silicone-modified polyurethane prepolymer Si-PUA is synthesized by reacting silicone with diisocyanate, and then a mixture of Si-PUA and PN halogen-free flame-retardant modified epoxy acrylic resin is sprayed on the surface of the base layer to form a low surface energy coating; then, an IEM-modified nano-SiO2 suspension is sprayed on the Si-PUA coating to form a double-layer structure, and cross-linking is carried out by a photoinitiator to improve the super hydrophobicity and flame retardant properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 IR spectra of polydimethylsiloxane-hydroxyl, PDMS-NCO and Si-PUA in Example 1;

[0047] Figure 2 is the infrared spectra of epoxidized m-xylylenediamine and phosphoric acid in Example 1;

[0048] Figure 3 The silicon dioxide and infrared spectra of IEM-SiO2 prepared in Example 1;

[0049] Figure 4 The thermal gravimetric test curves TG and DTG of the phosphorus-nitrogen halogen-free flame retardant modified epoxy acrylic resin and epoxy acrylic resin in air in Example 1;

[0050] Figure 5 TG curves of silicon dioxide and IEM-SiO2 in Example 1;

[0051] Figure 6 These are the results of the combustion experiment of the PN halogen-free flame retardant modified epoxy acrylic resin in Example 1; the first line is the combustion of epoxidized meta-phenylenediamine in Comparative Example 1 for 1 to 120 seconds; the second line is the first combustion for 1 to 100 seconds in Example 1; the third line is the second combustion for 1 to 48 seconds in Example 1.

[0052] Figure 7 Surface morphology of the coatings prepared in Examples 1 to 4 and Comparative Example 1; (a) to (e) are scanning electron microscope images of the coatings with IEM-SiO2 content in Comparative Example 1, Example 4, Example 3, Example 2, and Example 1, respectively; (f) is a further enlarged SEM image of the coating in Example 4;

[0053] Figure 8 is an AFM image of the coating prepared in Example 1;

[0054] Fig. 9 It is a line graph of the water contact angle values ​​of the coatings prepared in Examples 1 to 4 and Comparative Example 1.

[0055] Fig.10 The photographs are of water drops dropped on the coating formed by spraying the coating in Example 1 on different substrates; the substrates from left to right are plastic, paper, aluminum, and glass;

[0056] Fig.11 Figures 1 and 2 are the combustion process diagrams and oxygen index process diagrams of the coatings prepared on the FRP sample in Example 1 and Comparative Example 2; a is the combustion process diagram of the coating prepared on the FRP sample in Example 1; b is the combustion process diagram of the coating prepared on the FRP sample in Comparative Example 2; c is the oxygen index measurement process diagram of the coating prepared on the FRP sample in Comparative Example 2; d is the oxygen index measurement process diagram of the coating prepared on the FRP sample in Example 1;

[0057] Fig.12 The heat release rate of the coatings prepared in Comparative Example 2 and Examples 7 to 9 is a curve diagram of the change over time; FREP-0% is Comparative Example 2; FREP-10% is Example 7; FREP-20% is Example 8; FREP-30% is Example 9;

[0058] Fig.13 The total heat release (THR) of the coatings prepared in Comparative Example 2 and Examples 7 to 9 varies with time; FREP-0% is Comparative Example 2; FREP-10% is Example 7; FREP-20% is Example 8; FREP-30% is Example 9;

[0059] Fig.14The smoke release rate variation curves of the coatings prepared in Examples 7 to 9 of Comparative Example 2 are shown below; FREP-0% is Comparative Example 2; FREP-10% is Example 7; FREP-20% is Example 8; FREP-30% is Example 9;

[0060] Fig.15 These are the front view and top view of the carbon residue after combustion of the coatings prepared in Comparative Example 2 and Examples 7 to 9 after cone calorimeter testing; from left to right they are Comparative Example 2, Example 7, Example 8, and Example 9, respectively. DETAILED DESCRIPTION

[0061] Example 1

[0062] The first aspect of the present embodiment provides a flame retardant super hydrophobic coating, the components of which are component A and component B;

[0063] The component A comprises modified polyurethane prepolymer Si-PUA, modified epoxy acrylic resin, photoinitiator and organic solvent; the component B comprises modified nano silicon dioxide, photoinitiator and organic solvent.

[0064] The components of the component A are, by weight, 75 parts of modified polyurethane prepolymer Si-PUA, 20 parts of modified epoxy acrylic resin, 5 parts of photoinitiator and 400 parts of organic solvent.

[0065] The mass ratio of the modified nano-silicon dioxide, the photoinitiator and the organic solvent in the B component is 97:3:400.

[0066] The modified nano silicon dioxide accounts for 4wt% of the flame retardant super hydrophobic coating.

[0067] The modified polyurethane prepolymer Si-PUA is a polyurethane prepolymer Si-PUA modified by organic silicon.

[0068] The preparation method of Si-PUA comprises the following steps:

[0069] S1: In a N2 atmosphere at 45°C, the reaction of polydimethylsiloxane-hydroxyl and isophorone diisocyanate was initiated by dibutyltin dilaurate for 3 hours to obtain terminal isocyanate polyurethane PDMS-NCO;

[0070] S2: After reacting for 3 hours, the temperature was raised to 65° C., pentaerythritol triacrylate was added dropwise to the isocyanate-terminated polyurethane PDMS-NCO, and the reaction was continued for 3 hours to obtain a silicone-modified polyurethane prepolymer Si-PUA.

[0071] The molar ratio of the polydimethylsiloxane-hydroxyl group to isophorone diisocyanate is 2.1:1.

[0072] The added amount of dibutyltin dilaurate is one thousandth of the total molar amount of polydimethylsiloxane-hydroxyl and isophorone diisocyanate.

[0073] The molar ratio of the pentaerythritol triacrylate to the isocyanate-terminated polyurethane PDMS-NCO is 1:1.

[0074] The CAS number of the dibutyltin dilaurate is 77-58-7; the polydimethylsiloxane-hydroxyl is purchased from Wuhan Kemik Biopharmaceutical Technology Co., Ltd.; the CAS number of the isophorone diisocyanate is 4098-71-9; and the CAS number of the pentaerythritol triacrylate is 3524-68-3.

[0075] The modified epoxy acrylic resin is PN halogen-free flame-retardant modified epoxy acrylic resin.

[0076] The preparation process of the PN halogen-free flame-retardant modified epoxy acrylic resin is as follows: dissolving epoxidized m-xylylenediamine in 100 mL of acetone, then adding phosphoric acid and an inhibitor, stirring, reflux heating to 60° C., maintaining for 3 hours to obtain a reactant, then rotary evaporating to remove acetone in the reactant, and freeze-drying to remove moisture in the reactant to obtain a light yellow transparent solid; grinding with agate mortar, washing with ethyl acetate to remove unreacted reagents, and rotary evaporating and drying to obtain a light yellow powder, which is named PN halogen-free flame-retardant modified epoxy acrylic resin.

[0077] The molar ratio of the epoxidized meta-xylylenediamine to the phosphoric acid is 2:1.

[0078] The phosphoric acid is an 85 wt % phosphoric acid aqueous solution.

[0079] The inhibitor accounts for 0.1% of the total mass of epoxidized meta-xylylenediamine and phosphoric acid.

[0080] The polymerization inhibitor is p-hydroxyanisole.

[0081] The modified nano-silica is nano-silica modified by isocyanoethyl methacrylate (IEM).

[0082] The preparation method of the nano-silica modified by isocyanoethyl methacrylate (IEM) is as follows: drying the nano-silica in a vacuum oven at 200° C. for 2 hours, and then cooling it to 25° C.; dispersing it in ethyl acetate to obtain a nano-silica suspension; and then adding IEM and dibutyltin dilaurate to the nano-silica suspension respectively, stirring at 70° C. for 4 hours, and washing and drying to obtain the nano-silica modified by isocyanoethyl methacrylate (IEM).

[0083] The ratio of the nano-silicon dioxide to ethyl acetate is 1 g:50 mL.

[0084] The mass ratio of the IEM, dibutyltin dilaurate and nano-silicon dioxide is 3:0.02:1.

[0085] The CAS number of the isocyanoethyl methacrylate is 30674-80-7.

[0086] The photoinitiator is photoinitiator 1173.

[0087] The photoinitiator 1173 was purchased from Shanghai Kaiyin Chemical Co., Ltd., and the model number is Darocur 1173.

[0088] The organic solvent is ethyl acetate.

[0089] A second aspect of the present embodiment provides a method for using a flame retardant super hydrophobic coating, comprising the following steps:

[0090] M1: According to the mass parts of the flame retardant super-hydrophobic components, the Si-PUA prepolymer, PN halogen-free flame retardant modified epoxy acrylic resin and photoinitiator in component A are dissolved in an organic solvent to prepare a resin dispersion; then the resin dispersion is sprayed onto the substrate by a paint sprayer, and wait for 5 minutes to obtain a 10 μm modified polyurethane layer;

[0091] M2: After 5 minutes, the nano-silica modified with isocyanoethyl methacrylate (IEM), photoinitiator and ethyl acetate in component B were prepared into solution B using the same paint sprayer, sprayed evenly onto the modified polyurethane layer, and cured under ultraviolet light for 3 minutes to prepare a 10 μm flame-retardant super-hydrophobic coating.

[0092] The substrate is glass fiber reinforced plastic.

[0093] Example 2

[0094] The specific implementation of Example 2 is the same as that of Example 1, except that the modified nano-silica accounts for 3 wt % of the flame retardant super hydrophobic coating.

[0095] Example 3

[0096] The specific implementation of Example 3 is the same as that of Example 1, except that the modified nano-silica accounts for 2 wt % of the flame retardant super hydrophobic coating.

[0097] Example 4

[0098] The specific implementation of Example 4 is the same as that of Example 1, except that the modified nano-silica accounts for 1 wt % of the flame retardant super hydrophobic coating.

[0099] Comparative Example 1

[0100] The specific implementation of Comparative Example 1 is the same as that of Example 1, except that: the modified nano-silica accounts for 0wt% of the flame retardant super hydrophobic coating.

[0101] Comparative Example 2

[0102] The specific implementation of Comparative Example 2 is the same as that of Example 1, except that: the flame-retardant super-hydrophobic coating does not contain PN halogen-free flame-retardant modified epoxy acrylic resin.

[0103] Example 7

[0104] The specific implementation of Example 7 is the same as that of Example 1, except that: the PN halogen-free flame retardant modified epoxy acrylic resin accounts for 10wt% of the flame retardant super hydrophobic coating.

[0105] Example 8

[0106] The specific implementation of Example 8 is the same as that of Example 1, except that: the PN halogen-free flame retardant modified epoxy acrylic resin accounts for 20wt% of the flame retardant super hydrophobic coating.

[0107] Example 9

[0108] The specific implementation of Example 9 is the same as that of Example 1, except that: the PN halogen-free flame retardant modified epoxy acrylic resin accounts for 30wt% of the flame retardant super hydrophobic coating.

[0109] Performance Testing

[0110] 1. Use infrared spectrometer to measure the infrared spectra of polydimethylsiloxane-hydroxyl, PDMS-NCO, and Si-PUA respectively. The results are shown in Figure 1 .

[0111] Figure 1 As shown in the figure, the 2270 cm -1 At the same time, the stretching vibration peaks of C=O and NH appeared at 1724 cm -1 and 1535cm -1 , indicating that the preparation of PDMS-NCO was successful. Compared with the PDMS-NCO spectrum, the peak of C=C structural vibration in the Si-PUA spectrum appears at 1637 cm -1 The successful preparation of Si-PUA prepolymer was demonstrated.

[0112] The infrared spectra of epoxidized m-xylenediamine and phosphoric acid were measured by infrared spectrometer. The results are shown in Figure 2 .Depend on Figure 2 It can be seen that at 1212cm -1 and 1055cm -1The characteristic absorption peak of the POC bond at is consistent with the characteristic absorption peak of the aromatic POC bond, indicating that there is a ring-opening reaction between phosphoric acid and the epoxy group of epoxidized m-phenylenediamine, thereby producing PN halogen-free flame retardant modified epoxy acrylic resin hydroxyl group.

[0113] The silicon dioxide and infrared spectra of IEM-SiO2 were measured by FTIR spectrometer. The results are shown in Figure 3 . Figure 3 The two spectra at 1105 cm -1 There is a strong absorption peak at 3430cm -1 The stretching vibration peak of -OH was observed at 1730 cm-1. Compared with silica nanoparticles, there is an additional peak in the IEM-SiO2 spectrum, which is due to the stretching vibration of CH3. -1 and 1526cm -1 Some characteristic absorption peaks appeared at 1637cm -1 The vibration peaks of C=C structure were observed at . These additional peaks confirmed that the IEM was successfully introduced into the surface of silica nanoparticles.

[0114] 2. The phosphorus-nitrogen halogen-free flame retardant modified epoxy acrylic resin and epoxy acrylic resin AG-601 obtained in Example 1 were analyzed by thermogravimetric analyzer at 0-700°C, and the corresponding DTG was calculated by TG value. Figure 4 :from Figure 2 It can be seen that phosphorus-nitrogen halogen-free flame retardant modified epoxy acrylic resin begins to degrade at 286°C, the maximum mass loss rate occurs at about 537°C, and the stable solid residue mass fraction at 700°C is about 35.1wt%. AG-601 begins to degrade at 268°C, the maximum mass loss rate occurs at about 435°C, and the stable solid residue mass fraction at 700°C is about 9.5wt%.

[0115] Will Figure 4 The initial degradation temperature (Td) in the sample is 5 wt% and the temperature at which the weight loss is 5 wt% is T -5% , the midpoint temperature of degradation is T -50% The residual amount of solids at 700°C is recorded in Table 1. The initial degradation temperature (Td) of epoxidized m-phenylenediamine and the temperature at which the weight loss rate is 5wt% are T -5% , the midpoint temperature of degradation is T -50% The residual solid content at 600°C is recorded in Table 1.

[0116] Table 1

[0117] <![CDATA[T -5% (℃)]]> <![CDATA[T -50% (℃)]]> Char residue(%)at 700℃ Example 1 286 537 35.1 AG-601 268 435 9.5

[0118] Thermogravimetric analysis of IEM-SiO2 at 0-800°C was performed using a thermogravimetric analyzer. Figure 5 .

[0119] 3. UL-94 vertical burning test

[0120] Fix the standard sample vertically on the sample clamp, with the bottom 300 mm away from the horizontally laid medical absorbent cotton. Ignite the sample 10 mm below the lower end, and record the time it takes for the material to extinguish after two ignitions. The flammability of the material is divided into three levels: V-0, V-1 and V-2 according to the self-extinguishing time of each ignition and its sum, as well as whether there is dripping. The process diagram is shown in Figure 6 .

[0121] Table 2

[0122]

[0123] 4. Scan the coatings prepared in Examples 1 to 4 and Comparative Example 1 using a scanning electron microscope. Figure 7 .

[0124] Figure 7 The surface morphology of IEM-SiO2 / PN halogen-free flame retardant modified epoxy acrylic resin / Si-PUA coating (surface morphology of IEM-SiO2, PN halogen-free flame retardant modified epoxy acrylic resin and Si-PUA coating) is shown, and the IEM-SiO2 content is between 0wt% and 4wt%. (a) to (e) are scanning electron microscope images of the coatings with IEM-SiO2 content in Comparative Example 1, Example 4, Example 3, Example 2, and Example 1, respectively. (f) is a further enlarged SEM image of the coating in Example 4; the surface of the coating without any IEM-SiO2 is smooth. After adding 1wt% modified silica nanoparticles (Example 4), the surface of the coating is composed of protrusions and flat resins, indicating that the number of silica nanoparticles is insufficient to form a rough structure. When the content of silica nanoparticles is greater than 2wt%, IEM-SiO2 is evenly dispersed and completely covers the Si-PUA layer. At the same time, as the content of IEM-SiO2 increases, the surface roughness of the IEM-SiO2 / PN halogen-free flame retardant modified epoxy acrylic resin / Si-PUA coating continues to increase. By further enlarging the image in the coating of Example 4 ( Figure 7 f), it can be observed that many cavities are formed, which are able to accommodate air and reduce the contact area between the water droplet and the surface.

[0125] The microscopic and nanostructures of the coating were further verified by scanning with an atomic force microscope. Figure 8), there are evenly distributed protrusions, in which a large number of gaps are formed by the aggregation of silica nanoparticles, forming a micro-nano rough structure.

[0126] 5. The water contact angle WCA of the water droplets on the coating in Examples 1 to 4 and Comparative Example 1 was measured using a JC2000D4F contact angle measuring instrument. The results are shown in Fig. 9 .

[0127] Results Fig. 9 . The results show that the wettability of the coating is affected by the content of IEM-modified silica nanoparticles. The WCA of the coating surface increases dramatically from 105° without any silica nanoparticles to 140° with only 1wt% IEM-SiO2. At the same time, the hydrophobicity of the coating continues to increase with the increase of IEM-SiO2 content. In particular, when 4wt% modified silica nanoparticles are sprayed, the surface WCA is as high as 160°, the SA is 2°, and the surface has superhydrophobicity. Although the higher the IEM-SiO2 content, the better the hydrophobicity of the coating, excessive IEM-SiO2 will make the surface nanoparticle layer too thick, thereby weakening the mechanical properties of the coating.

[0128] The coating in Example 1 was sprayed on plastic, paper, aluminum and glass to form a coating. The water contact angle of the coating on various substrates was measured using a JC2000D4F contact angle measuring instrument. The results are shown in Fig.10 In addition, the superhydrophobic coating not only has excellent superhydrophobicity, but also has good adhesion to various substrates, such as Fig.10 As shown. In addition to aluminum, the prepared coating can also be formed on a variety of substrates such as plastic, paper, glass, etc.

[0129] 6. The coating of the coating in Example 1 and the coating of the coating in Comparative Example 2 were subjected to LOI and UL94 vertical combustion tests. The 3 mm glass fiber reinforced plastic sample sprayed with the coating of the coating in Example 1 and the coating of the coating in Comparative Example 2 was decomposed to perform a surface flame combustion test and photographed with a digital camera. The sample was cut into strips with a size of 6.5*3*150 mm to further test its oxygen index. The results are shown in Fig.11 .

[0130] like Fig.11 As shown, the FRP sample of the coating prepared in Comparative Example 2 burned immediately within 10 seconds of the start of ignition. However, after adding the PN halogen-free flame-retardant modified epoxy acrylic resin, it did not burn within 60 seconds of ignition. The results show that after adding the PN halogen-free flame-retardant modified epoxy acrylic resin, the surface of the material realizes carbonization and expansion of the surface resin layer after contacting the high temperature of the flame, forming a carbonized layer, isolating oxygen and flame, preventing the further spread of the flame, and achieving a flame retardant effect.

[0131] The burning behaviors of the coatings of Example 1 and Comparative Example 2 are recorded in Table 3.

[0132] Table 2 shows that the LOI value of the coating increased from 19.5% to 25.5% after adding PN halogen-free flame retardant modified epoxy acrylic resin, indicating that the modified flame retardant super hydrophobic coating is difficult to burn in the air. The above results confirm that the addition of PN halogen-free flame retardant modified epoxy acrylic resin greatly improves the flame retardant properties of the coating.

[0133] Table 3

[0134] Spraying Flame retardant time Flame Spread LOI data (%) Comparative Example 2 10 yes 19.5 Example 1 >60 no 25.5

[0135] 7. Cone calorimetry is an effective method to evaluate the combustion behavior of polymers. Various characteristic parameters can be obtained during the cone calorimetry test. HRR represents the heat release rate during combustion. The higher the HRR value, the easier the combustion behavior. THR represents the total heat release during the entire combustion process. The higher the THR value, the greater the fire hazard. The effective heat of combustion (EHC) can reflect the degree of combustible volatiles in gas phase combustion, and combined with the specific extinction area (SEA), it can be used to explore the flame retardant mechanism.

[0136] According to the national standard GB / T16172-2007, the combustion performance of the coatings prepared in Comparative Example 2 and Examples 7 to 9 was further investigated using a cone calorimeter. The results are shown in Table 4.

[0137] Table 4

[0138] <![CDATA[THR / (MJ / m 2 )]]> <![CDATA[pk-HRR / (kW / m 2 )]]> av-EHC / (MJ / kg) <![CDATA[av-SEA / (m 2 / kg)]]> Comparative Example 2 12.6 484.9 22.7 804.2 Example 7 9.3 420.2 20.3 675.1 Example 8 3.4 161.6 19.7 645.2 Example 9 3.2 153.9 19.2 580.9

[0139] The heat release rate (HRR) curves of the coatings prepared in Comparative Example 2 and Examples 7 to 9 over time are shown in Fig.12 Combined with Table 3, it can be seen that the HRR of the coating in Comparative Example 2 is the largest, and its peak heat release rate (pk-HRR) is 484.9kW / m 2 When 10% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, i.e., Example 7, the pk-HRR decreases to 420.2 kW / m 2 , the decrease is about 13%. When 20% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, that is, Example 8, pk-HRR is reduced to 161.6kW / m 2 , the decrease is about 65%. When 30% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, that is, Example 9, pk-HRR is reduced to 161.6kW / m 2, the decrease is about 68%. With the increase of the amount of PN halogen-free flame retardant modified epoxy acrylic resin added, the lower the HRR value, the more difficult the combustion behavior is, and the better the flame retardant effect is. The modification of PN halogen-free flame retardant modified epoxy acrylic resin has greatly reduced the heat release rate of Si-PUA / IEM-SiO2 resin coating, showing excellent flame retardant effect. It may be due to the synergistic flame retardant effect of phosphorus, nitrogen and silicon that the resin coating modified by PN halogen-free flame retardant modified epoxy acrylic resin has a high efficiency flame retardant effect.

[0140] The total heat release (THR) of the coatings prepared in Comparative Example 2 and Examples 7 to 9 is shown in the graph of the change over time. Fig.13 Combined with Table 3, it can be seen that the THR of the coating prepared in Comparative Example 2 is the largest, which is 12.6MJ / m 2 When 10% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, that is, after Example 7, THR is reduced to 9.3MJ / m2, a decrease of about 26%. When 20% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, that is, after Example 8, THR is reduced to 3.4MJ / m 2 , the decrease is about 73%. When 30% of PN halogen-free flame retardant modified epoxy acrylic resin is introduced, that is, Example 9, THR is reduced to 3.2MJ / m 2 , the decrease is about 75%. With the increase of the amount of PN halogen-free flame retardant modified epoxy acrylic resin added, the lower the THR value, the less the material is burned and decomposed, and the better the flame retardant effect. When the addition amount of PN halogen-free flame retardant modified epoxy acrylic resin increases from 10% to 20%, its HRR value and THR value have a leap-forward decrease, showing an excellent flame retardant effect, but when the addition amount increases to 30%, the HRR and THR values ​​are very close to the data of 20% addition amount. This may be because a sufficient amount of PN elements from PN halogen-free flame retardant modified epoxy acrylic resin and Si elements in the coating are needed to form a PN-Si flame retardant synergistic effect, promote the carbonization of the material, and achieve high-efficiency flame retardancy.

[0141] The average specific extinction area (SEA) is an important indicator of smoke density and an important parameter for evaluating the smoke emission of materials during combustion. The smoke release rate curves of the coatings prepared in Comparative Example 2 and Examples 7 to 9 are shown in FIG. Fig.14 As shown in Table 3, as the amount of PN halogen-free flame retardant modified epoxy acrylic resin added increases, the average effective combustion heat and total smoke production of the resin coating continue to decrease, further proving the excellent flame retardant effect of PN halogen-free flame retardant modified epoxy acrylic resin. This makes the coating in Example 1 a halogen-free flame retardant functional super hydrophobic resin coating.

[0142] 8. The coatings prepared in Comparative Example 2 and Examples 7 to 9 were tested by cone calorimeter to form a carbon layer morphology.

[0143] Cone calorimeter test of carbon residues after combustion of coatings in Comparative Example 2 and Examples 7 to 9. Fig.15 As shown, when the addition amount of PN halogen-free flame retardant modified epoxy acrylic resin is 0, that is, comparative example 2, the combustion of the resin coating is relatively complete, the carbon residue is small, and no continuous carbon layer is formed. With the increase of the content of PN halogen-free flame retardant modified epoxy acrylic resin, the P content increases, and the carbon residue of the resin coating increases significantly. When the amount of PN halogen-free flame retardant modified epoxy acrylic resin reaches 20%, that is, Example 7, some dense and continuous carbon layers are formed, and the silicon particles can promote the formation of a stable carbon layer, thereby playing a barrier role against heat, air and hydrolysis products, and achieving a flame retardant effect.

Claims

1. A flame retardant super hydrophobic coating, characterized in that, Its components include component A and component B; the component A includes modified polyurethane prepolymer Si-PUA, modified epoxy acrylic resin, photoinitiator and organic solvent; the component B includes modified nano-silicon dioxide, photoinitiator and organic solvent; The components of the component A include, by weight, 70 to 80 parts of modified polyurethane prepolymer Si-PUA, 15 to 25 parts of modified epoxy acrylic resin, 3 to 8 parts of photoinitiator and 450 to 550 parts of organic solvent; The mass ratio of the modified nano-silicon dioxide, the photoinitiator and the organic solvent in the B component includes 95-100: 1-5: 350-450; The modified polyurethane prepolymer Si-PUA is a polyurethane prepolymer Si-PUA modified by organic silicon; The modified epoxy acrylic resin is PN halogen-free flame-retardant modified epoxy acrylic resin; The preparation process of the PN halogen-free flame-retardant modified epoxy acrylic resin is as follows: dissolving epoxidized m-xylylenediamine in 50-200 mL acetone, then adding phosphoric acid, stirring with an inhibitor, reflux heating to 50-70° C., maintaining for 2-4 hours, obtaining a reactant, then removing the acetone in the reactant by rotary evaporation, and removing the water in the reactant by freeze drying to obtain a light yellow transparent solid; grinding with agate mortar, washing with ethyl acetate to remove unreacted reagents, and after rotary evaporation and drying, a light yellow powder appears, which is named as PN halogen-free flame-retardant modified epoxy acrylic resin; The molar ratio of epoxidized m-xylenediamine to phosphoric acid is (1.8-2.2):1; The inhibitor accounts for 0.1% of the sum of the mass of epoxidized meta-xylylenediamine and phosphoric acid; The modified nano-silica is nano-silica modified by isocyanoethyl methacrylate (IEM); The Si-PUA prepolymer, PN halogen-free flame-retardant modified epoxy acrylic resin and photoinitiator in component A are dissolved in an organic solvent to prepare a resin dispersion; the resin dispersion is then sprayed onto a substrate using a paint sprayer, and waited for 5 to 8 minutes to obtain a modified polyurethane layer of 5 to 10 μm; after 5 to 8 minutes, the nano-silica modified with isocyanoethyl methacrylate (IEM) in component B, the photoinitiator and ethyl acetate are prepared into a B solution using the same paint sprayer, and evenly sprayed onto the modified polyurethane layer, and cured under ultraviolet light for 3 to 5 minutes to prepare a flame-retardant super-hydrophobic coating of 5 to 10 μm.

2. The flame retardant super hydrophobic coating according to claim 1, characterized in that The preparation method of the silicone-modified polyurethane prepolymer Si-PUA comprises the following steps: S1: In a N2 atmosphere at 40-50°C, dibutyltin dilaurate is used to initiate the reaction of polydimethylsiloxane-hydroxyl and isophorone diisocyanate for 2-4 hours to obtain terminal isocyanate polyurethane PDMS-NCO; S2: After reacting for 2 to 4 hours, the temperature is raised to 60 to 70° C., pentaerythritol triacrylate is added dropwise to the isocyanate-terminated polyurethane PDMS-NCO, and the reaction is carried out for 2 to 4 hours to obtain a silicone-modified polyurethane prepolymer Si-PUA.

3. The flame retardant super hydrophobic coating according to claim 1, characterized in that The preparation method of the nano-silica modified by isocyanoethyl methacrylate (IEM) comprises: drying the nano-silica in a vacuum oven at 180-220° C. for 1.5-3 h, and then cooling to 25° C.; dispersing the nano-silica in ethyl acetate to obtain a nano-silica suspension; and then adding IEM and dibutyltin dilaurate to the nano-silica suspension respectively, stirring at 60-80° C. for 3-5 h, and washing and drying to obtain the nano-silica modified by isocyanoethyl methacrylate (IEM).

Citation Information

Patent Citations

  • Flame-retardant water-based paint and preparation method thereof

    CN110964364A

  • Halogen-free flame-retardant modified epoxy acrylic resin and preparation method thereof

    CN116804030A

Cited By

  • Preparation method of wear-resistant flame-retardant acrylic resin coating

    CN121825337A

  • A method for preparing a wear-resistant and flame-retardant acrylic resin coating

    CN121825337B